Probing the Charge Transfer in a Frustrated Lewis Pair by Resonance Raman Spectroscopy and DFT Calculations - Marques, Leandro Ramos; Ando, Rômulo Augusto (Chemphyschem, 2021)
A classical Lewis adduct derives from a covalent bond between a Lewis acid and a base. When the adduct formation is precluded by means of steric hindrance the association of the respective acid‐base molecular system is defined as a frustrated Lewis pair (FLP). In this work, the archetypal FLP Mes3P/B(C6F5)3 was characterized for the first time by resonance Raman spectroscopy, and the results were supported by density functional theory (DFT) calculations. The charge transfer nature of the lowest energy electronic transition, from phosphine to borane, was confirmed by the selective enhancement of the Raman bands associated to the FLP chromophore at resonance condition. Herein, we demonstrate the use of resonance Raman spectroscopy as a distinguished technique to probe the weak interaction involved in FLP chemistry. The archetypal Mes3P/B(C6F5)3 frustrated Lewis pair (FLP) is characterized by Raman spectroscopy. The charge‐transfer interaction originating from the FLP encounter complex is probed by resonance Raman spectroscopy, where an enhancement of the bands assigned to the vibrational modes of both species confirms the chromophore regarding the electronic transition from the donor to acceptor orbitals.